A study to assess contraceptive use among married women in urban and rural areas: a comparative study - Gore, Sushma; Katkuri, Sushma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A high level of unmet need for contraception persists among currently married women in South Asia. At least 1 in 5 currently married women in the countries surveyed want to stop or delay childbearing, but are not using contraception. Therefore, many countries consider limiting population growth as an important component of their overall developmental goal to improve living standards and the quality of life of the people. The aim of the study was to assess knowledge, attitude and practices about contraceptive methods among married women in two different settings. Methods: A cross-sectional study was conducted in the outpatient department of obstetrics and gynecology at Shri Vasantrao Naik Government Medical College Yavatmal, Maharashtra for a period of two months from January 2012-February 2012. A total of 606 participants were surveyed in that two month duration. In Urban area-296 and in rural area, a total of 310 were covered. Results: Majority of the study participants were in the age group of 26-35 contributing to 46% in rural area and 37% in urban area. Awareness about contraception was good among rural area (83%) than urban area (63%). Study shows that more than 50% of the participants in both the areas were using contraceptive methods, rural (63%) and urban (53%). Conclusions: Promotion of contraceptive usage should be done by intense awareness campaigns.